50 years of the Nobel Prize to Lorenz, Tinbergen, and von Frisch: integrating behavioral function into an ethology for the 21st century - Font, Enrique (Frontiers in Ethology, 2023)
The 50th anniversary of the awarding of the Nobel Prize to Konrad Lorenz, Niko Tinbergen, and Karl von Frisch, arguably one of the most significant events in the history of ethology, has gone virtually unnoticed. Students and newcomers to the field may be wrongly led to believe that ethology has lost its prominent role as the leading discipline at the forefront of studies of animal behavior with a biological foundation. However, the decline of ethology is more apparent than real, in part a consequence of tying the discipline to a particular theoretical approach (i.e., that of classical ethology), but also due to the historical amnesia affecting many areas of science and the uneasy relationship of ethology with some of its own subdisciplines. Behavioral ecology emerged in the 1970s as an ethological subdiscipline devoted to the study of behavioral function, one of the four aims of ethology famously identified by Tinbergen. Behavioral ecology became extremely popular, but was criticized due to its narrow focus on behavioral function. With the new millennium came a return to a more balanced approach to the study of animal behavior, with frequent calls to recover the balance between the different areas of study and the integrative spirit that many consider one of the most distinctive features of ethology. Still, some behavioral ecologists contend that ethology disappeared shortly after Lorenz, Tinbergen, and von Frisch’s Nobel Prize award and has been replaced by behavioral ecology, and offer revisionist narratives of the aims and scope of both disciplines in support of this contention. Contrary to this view, modern ethology remains a necessary and coherent endeavor that encompasses and subsumes all four of Tinbergen’s aims, including those considered to be part of the agenda of behavioral ecology. The challenge for the next 50 years will be to preserve the ethological legacy of pursuing the four aims and their integration across levels of biological organization, taxa, methodologies, and interdisciplinary boundaries for a complete understanding of animal behavior.